Breast desmoid tumor after augmentation mammoplasty: two case reports - Mazzocchi, M; Onesti, M G; Di Ronza, S; Scuderi, N (Acta chirurgiae plasticae, 2009)
Desmoid tumor of the breast is a rare fibroblastic disease, a slow-growing and histologically benign lesion that accounts for 0.2% of all breast tumors. It can arise either primarily from the breast parenchyma or, by secondary invasion, from the muscolo-aponeurotic layer of the pectoral muscles. These tumors do not metastatize, have no capsule but do have the propensity to aggressively invade local tissues and organs. It has been suggested that these tumours are associated with surgical and non-surgical tissue trauma, certain hormones and genetic susceptibility. We describe two cases of breast desmoid tumor after breast augmentation. A 52-year-old caucasian woman and 38-year-old caucasian woman presented for a breast implant change. During surgery an inelastic, soft, capsulated mass, arising from the periprosthetic capsula in the area of pectoralis major muscle was found. The mass was removed en bloc together with a portion of the periprosthetic capsula, the resection including a portion of the pectoralis major muscle fascia in both cases. The results of this histological examination suggested an extra-abdominal desmoid tumor. To date both the local and the general conditions of the two patients are good, with no signs of recurrence of the lesion.
Keywords: Desmoid Tumors; implantace prsní náhrady; nádory prsu; Middle Aged; ženské pohlaví; Breast Neoplasms; dospělí; Device Removal; Humans; Adult; Breast Implantation; Female; odstranění implantátu; pooperační komplikace; Postoperative Complications; lidé středního věku; lidé; agresivní fibromatóza